NILAI KARAKTER DALAM KUMPULAN CERPEN GALUH SAKINDIT KISDAP BANJAR KARYA JAMAL T. SURYANATA (THE CHARACTER VALUE IN A COLLECTION OF SHORT STORIES GALUH SAKINDIT KISDAP BANJAR BY JAMAL T. SURYANATA) - Riza Abadi (Universitas Lambung Mangkurat, 2023)
AbstractThe Character Value In a Collection of short Stories Galuh Sakindit Kisdap Banjar by Jamal T. Suryanata. This research aims to knowing the character values short stories and the application of the character’s values in social life. The method in this research is a qualitative method with content analysis method. This research type is documentation with technique that is data collecting, selecting data, analyzing data in table, and concluding data. By using this method is expected the research can produce the purpose which with what is expected researcher. The researcher takes data as many as ten short stories in Banjar language. The character value contained in a Collection of Short Stories GaluhSakinditKisdap Banjar by Jamal T. Suryanata refers to 18 characters values, which are: religious, honest, toleracet, discipline, hard work, creative, independent, democratic, curiosity, nationality’s spirit or nationalism, love of the country, appreciate the achievement, communicative, like in peace, like to read, cares to environment, cares to social, and responsibility. Character value’s form in social life depends on awareness-self in importance to be a moral nation generation, good morals, and self responsible, social, and nation.Keywords: character value, short stories, Banjar languageAbstrakNilai Karakter dalam Kumpulan Cerpen Galuh Sakindit Kisdap Banjar karya Jamal T. Suryanata. Penelitian ini bertujuan untuk mengetahui nilai karakter dan penerapan nilai karakter itu dalam kehidupan bermasyarakat. Metode dalam penelitian ini merupakan metode kualitatif dengan metode analisis data. Jenis penelitian ini adalah dokumentasi dengan teknik pengumpulan data yakni (1) pengumpulan data, (2) penyeleksian data, (3) menganalisis data dalam tabel, dan (4) menyimpulkan data. Peneliti mengambil data sebanyak 10 cerpen bahasa Banjar. Nilai karakter yang terdapat dalam kumpulan cerpen mengacu kepada 18 nilaikarakter, yaitu: religius, jujur, toleransi, disiplin, kerjakeras, kreatif, mandiri, demokratis, rasa ingin tahu, semangat kebangsaan atau nasionalisme, cinta tanah air, menghargai prestasi, komunikatif, cinta damai, gemar membaca, peduli lingkungan, peduli sosial, dan tanggung jawab. Wujud nilai karakter dalam kehidupan bermasyarakat bergantung kepada kesadaran diri akan pentingnya menjadi generasi bangsa yang bermoral, berakhlak baik, dan bertanggungjawab terhadap diri sendiri, masyarakat, dan bangsa.Kata Kunci: nilai karakter, cerpen, bahasa banjar